2022
DOI: 10.3390/ijms23010533
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol in the Cell Membrane—An Emerging Player in Atherogenesis

Abstract: Membrane cholesterol is essential for cell membrane properties, just as serum cholesterol is important for the transport of molecules between organs. This review focuses on cholesterol transport between lipoproteins and lipid rafts on the surface of macrophages. Recent studies exploring this mechanism and recognition of the central dogma—the key role of macrophages in cardiovascular disease—have led to the notion that this transport mechanism plays a major role in the pathogenesis of atherosclerosis. The exact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 85 publications
0
20
0
2
Order By: Relevance
“…Our preliminary data [ 13 ] documented a significant positive correlation between the proportion of PIMs and non-HDL cholesterol levels in a relatively small number of LKDs. We, herein, present this correlation in 154 LKDs ( Figure 3 ) [ 26 ]. On the one hand, the highly significant correlation demonstrated that, in individuals with low non-HDL cholesterol levels, the proportion of PIMs was about 20%.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Our preliminary data [ 13 ] documented a significant positive correlation between the proportion of PIMs and non-HDL cholesterol levels in a relatively small number of LKDs. We, herein, present this correlation in 154 LKDs ( Figure 3 ) [ 26 ]. On the one hand, the highly significant correlation demonstrated that, in individuals with low non-HDL cholesterol levels, the proportion of PIMs was about 20%.…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, a decrease in cholesterol inflow to the artery may start a reversal of atherosclerosis and reduce the likelihood of atherosclerosis-related complications [ 28 ]. In addition, there may also be decreased transport of cholesterol molecules to the lipid rafts in circulating monocytes [ 26 ]. The documented decrease in non-HDL cholesterol levels and the shift of the general population to lower cholesterol levels, thus, resulted in lowering CVD mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, chol depletion leads to increased PS exposure at the surface of RBCs, suggesting a role of chol as phospholipid scrambling regulator ( Arashiki et al, 2016 ). Second, the inner leaflet chol appears to be involved in diverse cellular processes such as modulation of cytoskeleton and motility and neurotransmitter receptor trafficking ( Paukner et al, 2022 ).…”
Section: Physiological Cholesterol Homeostasis Roles and Membrane Dis...mentioning
confidence: 99%
“…Following the biosynthesis, desaturase enzymes introduce a methylene group in saturated FA (SFA) leading to the monounsaturated FA (MUFA), while polyunsaturated FA (n‐6 and n‐3 PUFA) are produced by elongation and desaturation of the essential linoleic (18:2 n‐6) and α‐linolenic (18:3 n‐3) acids, respectively (Ferreri et al, 2016 ; Maulucci et al, 2016 ). Free cholesterol, together with phospholipids, is an essential component in the plasma membrane of mammalian cells and plays diverse structural and functional roles (Paukner et al, 2022 ). Changes in lipid organization (FA and cholesterol) can largely affect membrane functional and biophysical properties (fluidity and lipid rafts organization), severely altering cellular functions such as membrane trafficking, protein dynamics, and signal transduction (Ferreri et al, 2016 ; Maulucci et al, 2016 ; Paukner et al, 2022 ; Santos & Schulze, 2012 ).…”
Section: Introductionmentioning
confidence: 99%